Schema therapy for Dissociative Identity Disorder: a case report - Bachrach, Nathan; Rijkeboer, Marleen M.; Arntz, Arnoud; Huntjens, Rafaële J. C. (Frontiers in Psychiatry, 2023)
Treatment for Dissociative Identity Disorder (DID) often follows a practice-based psychodynamic psychotherapy approach which is conducted in three phases, i.e., symptom stabilization, trauma processing, and identity integration and rehabilitation. The percentage of patients that reaches the third phase is relatively low, treatment duration is long, and the effects of this treatment on the core DID symptoms have been found to be small or absent, leaving room for improvement in the treatment of DID. Schema Therapy (ST) is an integrative psychotherapy that has been proposed as a treatment for DID. This approach is currently being investigated in several studies and has the potential to become an evidence-based treatment for DID. This case report presents an overview of the protocol adaptations for DID ST treatment. The presented case concerns a 43-year-old female patient with DID, depressive disorder (recurrent type), PTSD, cannabis use disorder, and BPD. Functioning was very low. She received 220 sessions of ST, which included direct trauma processing through Imagery Rescripting (ImRs). The patient improved in several domains: she experienced a reduction of PTSD symptoms, as well as dissociative symptoms, there were structural changes in the beliefs about the self, and loss of suicidal behaviors. After treatment she was able to stop her punitive mode, to express her feelings and needs to others, and to participate adequately in social interaction. This case report indicates that ST might be a viable treatment for DID, adding to a broader scope of treatment options for this patient group.